2020
DOI: 10.3390/ijms21082753
|View full text |Cite
|
Sign up to set email alerts
|

The Expression Profile of Dental Pulp-Derived Stromal Cells Supports Their Limited Capacity to Differentiate into Adipogenic Cells

Abstract: Mesenchymal stromal cells (MSCs) can self-renew, differentiate into specialised cells and have different embryonic origins-ectodermal for dental pulp-derived MSCs (DPSCs) and mesodermal for adipose tissue-derived MSCs (ADSCs). Data on DPSCs adipogenic differentiation potential and timing vary, and the lack of molecular and genetic information prompted us to gain a better understanding of DPSCs adipogenic differentiation potential and gene expression profile. While DPSCs differentiated readily along osteogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Due to existing reports indicating that DPSCs have a limited capacity to differentiate into adipocytes [ 22 , 23 , 24 ], we first explored the conditions to induce the adipogenic response in those stem cells by comparing them in five adipogenic cocktails ( Table 1 ). As the starting point, we used an adipogenic induction medium 1 (AIM-1, see Table 1 ), which was enriched with 10 μM of INS and 200 μM of INDO, potent adipogenic agents that stimulate the proliferation and differentiation of preadipocytes by triggering the expression of essential transcriptional factors governing adipogenesis [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to existing reports indicating that DPSCs have a limited capacity to differentiate into adipocytes [ 22 , 23 , 24 ], we first explored the conditions to induce the adipogenic response in those stem cells by comparing them in five adipogenic cocktails ( Table 1 ). As the starting point, we used an adipogenic induction medium 1 (AIM-1, see Table 1 ), which was enriched with 10 μM of INS and 200 μM of INDO, potent adipogenic agents that stimulate the proliferation and differentiation of preadipocytes by triggering the expression of essential transcriptional factors governing adipogenesis [ 25 , 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…The inhibition of this protein by bpV (pic) or the PTEN knockdown induces the expression of PPAR γ and LPL , and increases the adipogenic response of DPSCs by suppressing the osteogenic pathway [ 60 ]. More recently, despite the fact that DPSCs exhibit MSCs and stemness features, this cell population is unable to differentiate into adipocytes [ 22 ] even by using a commercial culture induction media [ 23 ]. The detailed analysis of the transcriptomic data showed that DPSCs, when cultured under adipogenic conditions, express genes that inhibit adipogenic differentiation, including the wingless-type member 10 ( WNT10B ) or MSH-like homeobox ( MSX2 ) [ 23 ], which can prevent adipogenesis by blocking the expression of PPAR γ and the C/EBP family [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, DPSCs cultured in the adipogenic induction medium did not show cytoplasmic lipid accumulation and had low expression levels of adipogenic-related genes (Fracaro et al, 2020). A recent study disclosed the gene expression profile of DMSCs, which supported their limited capacity of differentiating into adipocytes (Fracaro et al, 2020). However, it seems that the adipogenic limitation is not insurmountable.…”
Section: Adipogenesismentioning
confidence: 99%
“…Although some studies have reported that DMSCs can achieve adipogenic differentiation as efficiently as other MSCs, sometimes their conclusions were based solely on microscopic images of a few differentiated cells without further confirmation (Gronthos et al, 2000;Isobe et al, 2016). Meanwhile, DPSCs cultured in the adipogenic induction medium did not show cytoplasmic lipid accumulation and had low expression levels of adipogenic-related genes (Fracaro et al, 2020). A recent study disclosed the gene expression profile of DMSCs, which supported their limited capacity of differentiating into adipocytes (Fracaro et al, 2020).…”
Section: Adipogenesismentioning
confidence: 99%
“…In this regard, DPSCs exhibit higher mineralization capacity than other MSCs, including BMSCs, ATSCs, and different DT-MSCs (Xu et al, 2013;Padial-Molina et al, 2019;Shen et al, 2019;Mucientes et al, 2021). Thus, not surprisingly, the hypomethylation of the WNT10B locus (Figure 1G) facilitates its expression in DPSCs (Fracaro et al, 2020) to favor osteogenesis over adipogenesis, which suggests that DNA methylation is a mechanism underlying adipocyte and bone cell development. Together, these findings allow us to hypothesize that both the DNA methylation and gene expression established in DPSCs tend to be preserved, which suggests that the higher DNMT expression in DPSCs but not in PLSCs may be an important mechanism of cell identity that maintains the integrity of the epigenetic memory of DPSCs even under adipogenic conditions.…”
Section: Discussionmentioning
confidence: 93%